Cancer drug prices in the United States: efficacy, innovation, clinical trial evidence, and epidemiology - Michaeli, Daniel; Michaeli, Christoph T. (Value in health, 2023)
Objectives - Rising cancer drug prices challenge patients and healthcare systems. Although prices are routinely assigned to original drug indications receiving US Food and Drug Administration (FDA) approval, the pricing of supplemental indication approvals remains uncertain. This study identifies and quantifies factors associated with cancer drug prices, distinctly analyzing original and supplemental indications. - Methods - Clinical trial evidence and epidemiologic data supporting new indications’ FDA approval (2003-2022) were collected from the DrugsFDA database, ClinicalTrials.gov, and Global Burden of Disease study. Indication-specific monthly treatment costs were calculated for Medicare patients. The association between log-prices and collected variables were assessed in regression analyses. - Results - We identified 145 drugs approved across 373 cancer indications. Drugs were priced at $24 444 per month on average (median = $16 013). For original indications, prices weakly correlated to improvements in overall survival (β = 0.28, P = .037) and progression-free survival (β = 0.16, P = .001). Original indications’ prices were as follows: (1) negatively associated with disease incidence (β = −0.21, P < .001) and prevalence; (2) positively correlated with first-in-class drugs (26%, P = .057), gene and cell therapies (176%, P < .001), hematologic cancers (62%, P < .001), and severe diseases with substantial unmet needs (6% per disability-adjusted life-year, P < .001); and (3) negatively correlated to indications with randomized-controlled phase 3 trials. Prices were poorly associated with supplemental indications’ efficacy, clinical evidence, and epidemiology. - Conclusions - Cancer drug prices are set based on the original indication’s characteristics, thereby omitting the value of supplemental indications. Indication-specific pricing, coverage, and reimbursement policies considering each indication’s safety, efficacy, innovativeness, and unmet needs are necessary to align a drug’s value and price.
Online verfügbar 28 July 2023, Version des Artikels 27 October 2023
Gesehen am 18.01.2024